The repair of large thoracoabdominal gaps using synthetic meshes - Cottini, Guillermo F (Cirugía del Uruguay, 2020)
The location of malignant tumors in the thoracoabdominal walls, whether they are primitive or secondary, requires very extensive resections, which sometimes pose difficult problems for the surgeon ...